Making Thinking Visible : How to Promote Engagement, Understanding, and Independence for All Learners - Ritchhart, Ron, 1958-; Church, Mark, 1970-; Morrison, Karin, 1951- (San Francisco, CA : Jossey-Bass, 2011)
'Visible Thinking is a research-based approach to teaching thinking that develops students' thinking dispositions, while at the same time deepening their understanding of the topics they study. Rather than a set of fixed lessons, Visible Thinking is an extensive and adaptable collection of practices that include thinking routines and the documentation of student thinking. The routines are a central element of the practical, functional and accessible nature of Visible Thinking. Thinking routines are easy to use mini-strategies that are repeatedly used in the classroom. They are a small set of questions or a short sequence of steps that can be used across various grade levels and content. Each routine targets a different type of thinking and by bringing their own content, teachers can integrate the routines into the fabric of their classrooms. Thinking Routines help direct student thinking and structure classroom discussion. Thinking becomes visible as the students' different viewpoints are expressed, documented, discussed and reflected upon'--
Book is accompanied by 1 videodisc entitled'Making Thinking Visible : How to Promote Engagement, Understanding, and Independence for All Learners' bearing the same call number and available at Bahagian Koleksi Media'
Includes bibliographical references (pages 275-280) and index.
Keywords: Thought and thinking -- Study and teaching; Critical thinking -- Study and teaching; Cognition in children